1994
DOI: 10.1136/oem.51.6.361
|View full text |Cite
|
Sign up to set email alerts
|

Hand-arm vibration syndrome among travertine workers: a follow up study.

Abstract: In a six year follow up study of the handarm vibration syndrome, 62 stoneworkers operating hand held vibrating tools in 10 travertine quarries and mills were first investigated in 1985 and then in 1991. The frequency weighted acceleration ofvibration from the rock drills and stone hammers used by the travertine workers exceeded 20 m/s2, indicating a hazardous work activity according to the proposal of the EC directive for physical agents. A clinical examination and a cold provocation test were repeated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Thus, VWF can improve to some extent when vibration exposure is stopped or reduced. On the other hand, several studies have indicated that VWF persisted even after vibration exposure ceased or was reduced (Agate 1949;Jepson 1954;Dandanell et al 1993;Bovenzi et al 1994). In the present study, VWF persisted in about 70% of patients with VWF during the 6-year follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, VWF can improve to some extent when vibration exposure is stopped or reduced. On the other hand, several studies have indicated that VWF persisted even after vibration exposure ceased or was reduced (Agate 1949;Jepson 1954;Dandanell et al 1993;Bovenzi et al 1994). In the present study, VWF persisted in about 70% of patients with VWF during the 6-year follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…Investigations of vibration-exposed worker groups other than chain-saw operators have produced contrasting results. VWF symptoms were reported to improve, remain unchanged, or deteriorate after the cessation of vibration exposure [1,2,6,10,19]. Most follow-up studies of the reversibility of VWF, however, have been based on anamnestic ®ndings.…”
Section: Introductionmentioning
confidence: 97%
“…Subjective improvements in the extent and frequency of ®nger-blanching attacks or complete remissions of vascular complaints have been reported in both active and retired forestry workers [10,18,20]. Some of these studies evidenced the natural course of VWF by means of objective clinical tests in addition to anamnestic ®ndings [3,30,33].…”
Section: Discussionmentioning
confidence: 94%
“…HAVS patients with VWF symptoms were reported to improve, remain unchanged, or deteriorate after the cessation of vibration exposure [3,30]. It has been shown in some epidemiological studies that symptoms of VWF may reverse if vibration exposure is reduced or ceased [4,8,10].…”
Section: Discussionmentioning
confidence: 97%